2015
DOI: 10.1039/c5ra01829c
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the roles of two constituents CL-20 and HMX in the CL-20:HMX cocrystal at high pressure: a DFT-D study

Abstract: The two constituents HMX and CL-20 produce different effects on the crystal structure of their cocrystal in different directions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 39 publications
1
15
1
Order By: Relevance
“…Most of the elastic constants show a remarkably increasing trend with the increasing pressure. C 15 and C 35 are found to be negative in a wide pressure region, which has been supported by Liu . In the pressure region of 0–15 GPa except for zero pressure, there exists a small difference among the elastic constants for C 11 , C 22 , and C 33 , satisfying the relationship of C 11 ≈ C 33 > C 22 .…”
Section: Resultssupporting
confidence: 57%
See 3 more Smart Citations
“…Most of the elastic constants show a remarkably increasing trend with the increasing pressure. C 15 and C 35 are found to be negative in a wide pressure region, which has been supported by Liu . In the pressure region of 0–15 GPa except for zero pressure, there exists a small difference among the elastic constants for C 11 , C 22 , and C 33 , satisfying the relationship of C 11 ≈ C 33 > C 22 .…”
Section: Resultssupporting
confidence: 57%
“…C 15 and C 35 are found to be negative in a wide pressure region, which has been supported by Liu. [24] In the pressure region of 0-15 GPa except for zero pressure, there exists a small difference among the elastic constants for C 11 , C 22 , and C 33 , satisfying the relationship of C 11 % C 33 > C 22 . It is suggested that the crystal shows much softness along a and c axes than b axis.…”
Section: Elastic Constants and The Related Propertiesmentioning
confidence: 84%
See 2 more Smart Citations
“…As early as in 1978, the 1,3,5,7-tetranitro-1,3,5,7-tetrazocane/ammonium perchlorate (HMX/AP) cocrystal was prepared by a decompression solvent evaporation method in which the hydrophobicity of AP was substantially improved. 10 Subsequently, researchers prepared 2,4,6,8,10,12-hexanitro-2,4,6,8,10,12-hexaazaisowurtzitane/2,4,6-trinitrotoluene (CL-20/ TNT), 11 CL-20/HMX, [12][13][14] 2,4,6,8,10,12-hexanitro-2,4,6,8,10,12hexaazaisowurtzitane/dinitrobenzene (CL-20/DNB), 15 1,3,5triamino-2,4,6-trinitrobenzene/1,3,5,7-tetranitro-1,3,5,7-tetrazocane (TATB/HMX), 16 and other cocrystal explosives [17][18][19] and reduced the sensitivity of explosives to a certain extent. For example, the nano CL-20/HMX explosive was prepared with the spray drying method.…”
Section: Introductionmentioning
confidence: 99%